ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Immune resistance in solid tumors is sustained by the coexistence of physical exclusion and immunological suppression, yet biomaterial strategies that coordinately address both barriers remain limited. Here, we report a single-component selenium-photothermal peptide conjugate, IR820-SFM Se , that self-assembles into a supramolecular nanoplatform and coordinates stromal remodeling with HLA-E/Qa-1 checkpoint modulation for NK-cell-oriented cancer immunotherapy. IR820-SFM Se self-assembled into nanoscale spherical structures and displayed enhanced near-infrared photothermal performance under 808 nm irradiation. The selenium-containing module downregulated HLA-E in human breast cancer cells and Qa-1 in murine 4T1 cells, which was accompanied by enhanced NK-92-mediated cytotoxicity and inflammatory cytokine expression. Upon laser irradiation, IR820-SFM Se induced localized photothermal heating, triggered immunogenic cell death, and altered stromal and vascular architecture. In bilateral 4T1 models, this coordinated strategy markedly inhibited both primary and distant tumors, accompanied by enhanced NK-cell activation, dendritic cell maturation, increased T-cell infiltration, and elevated systemic IFN-γ and TNF-α levels. These results demonstrate that coordinated physical and immunological remodeling of the tumor microenvironment can improve the responsiveness of immune-resistant tumors. Our study establishes a supramolecular biomaterial framework for overcoming dual barriers in solid tumor immunotherapy.